Factors Constraining Subject Expression in European Portuguese Spoken in Hamburg. A Bi-Generational Corpus Investigation - Cristina Flores; Esther Rinke (Discours)
The present study investigates subject expression in two generations of Portuguese migrants living in Hamburg, Germany. Based on a corpus of oral speech, we aim to assess whether second generation heritage speakers (HSs) differ from first generation migrants with respect to the factors constraining subject realisation/omission in European Portuguese (EP), a null subject language, in contact with German, a non-null subject language. The results do not reveal evidence in favour of ongoing language change, given that there are neither quantitative nor qualitative differences between the two generations of speakers. They show very similar overall rates of subject omission (around 67%) and they reveal sensitivity to the very same determining factors of subject pronoun realisation/omission, namely person and number, verb type, switch reference (topic continuity [TC]/topic shift [TS]) and distance. This finding is in line with previous corpus studies investigating the spontaneous speech of different generations of bilingual speakers or comparing monolingual and bilingual speakers of the same null subject language (e.g., Flores-Ferrán, 2004; Nagy, 2015). We conclude that language contact per se does not necessarily lead to a diverging grammar at an inter-generational level, as long as stable input conditions allow for the acquisition of the constraints that are valid for null subject languages.